Beyond Warmth and Competence: Influencer Marketing in Indonesia’s Local Fashion - Andina Fasha; Ratih Anggraini; Lily Purwianti; Teh Zaharah Yaacob (Penerbit Goodwood, 2026)
Purpose: This study investigates the impact of brand warmth and brand competence on consumers repurchase intentions for local fashion brands in Indonesia, focusing on Batam City. Grounded in the Theory of Planned Behavior (TPB) and the Stereotype Content Model (SCM), this study examines consumer engagement as a mediating factor and influencer marketing as a moderating variable. Research Methodology: A quantitative method was employed, and responses from 446 participants in Indonesia were collected using structured questionnaires. Data were analyzed using SmartPLS 3. Results: The findings revealed that brand warmth significantly enhanced repurchase intention, whereas brand competence did not. However, warmth and competence substantially increased consumer engagement, positively mediating the relationship with repurchase intention. Additionally, influencer marketing strengthens the effect of brand perception on consumer engagement. Conclusions: These insights suggest that emotional perception (warmth) is a stronger driver of consumer loyalty than functional perception (competence), and that influencer-driven strategies can effectively boost brand-consumer connections. Limitations: This study focuses only on local fashion brands in Indonesia, especially bags and wallets; therefore, the results may not apply to other products or industries. The study was conducted only in Indonesia and mainly involved female consumers. Contributions: This study makes a significant theoretical contribution by integrating the TPB and SCM into the local branding context, particularly by emphasizing emotional branding and influencer partnerships to enhance sustained consumer engagement and loyalty in the competitive local fashion market.